Choreography of space: fusing architecture and dance - Saldanha, Dwayne (My University, 2012)
It is unlikely that every human society at any given time has denied itself the excitement and pleasure of dance. Unlike cave paintings that have been brushed onto rocks lasting for centuries, dance in its nature leaves no trace. The footsteps of one trying to appease the spirits or prints in the sand left by one boogie for right of passages get covered over and forgotten. Yet the spaces for these activities become indelible imprinted into our minds and hearts. Formalization of space for dance is seen through the celebrations and performance which was a source of entertainment for kings and on lookers. It is overwhelmingly how entrenched dance is in South African’s lives. This is so Evident, from the poppies (or better known as the coloured comminute in Cape Town) lively jive. To the Zulu’s with their Indlamu - the traditional dance performed by the warriors. The toyi toyi often regarded as ‘the dance of defiance’ Hence it can be said that dance has a pertinent and relevant historic, spatial and social dimension. This essay will critical discuss these spatial dimensions of dance. Revealing that the urban scars of Apartheid still limit this social and physical activity. The investigation of the space used for dance in the area will reveal not only if it’s inadequate architecturally, but also the important role dance plays in the lives of Soweto inhabitants. The proposed intervention emerges directly from this manifestation of research- where dance is not only a recreational activity unifying people from all corners of the area together onto one floor. But also • An expression of what, and who we are. As individuals and as a nation. • It could be a place of healing • A place of refuge from the dangers. I.e. for young ones (getting them off the streets and away from drugs, crime, etc.) • Dance as a ritual, celebration, and mourning. Also the amalgamation of dance styles that are being taught and studied from contemporary Latin American, ballroom, ballet. Fusing these styles and required spaces together (unity through diversity), will gesture to the present hybrid society we find ourselves in. and also where the local passion for dance, is no longer undermined and where a sense of community can be seen and encouraged through a place for dance